Isolated splenic metastasis from primary fallopian tube carcinoma and the application of laparoscopic splenectomy: a case report and literature review - Kang, Dongxue; Zhao, Danyang; Jiang, Xiaodi; Li, Deming (Frontiers in Oncology, 2023)
Metastases to the spleen from various non-hematologic malignancies are generally not a common clinical event and usually indicate the late dissemination of disease. Solitary splenic metastases from solid neoplasm are extremely uncommon. Furthermore, solitary metastasis to the spleen from primary fallopian tube carcinoma (PFTC) is extremely rare and has not been reported previously. We report a case of isolated splenic metastasis in a 60-year-old woman, occurring 13 months after a total hysterectomy, a bilateral salpingo-oophorectomy, a pelvic lymphadenectomy, a para-aortic lymphadenectomy, an omentectomy, and an appendectomy were performed for PFTC. The patient’s serum tumor marker CA125 was elevated to 49.25 U/ml (N < 35.0 U/ml). An abdominal computed tomography (CT) scan revealed a 4.0 × 3.0 cm low-density lesion in the spleen that was potentially malignant, with no lymphadenectasis or distant metastasis. The patient underwent a laparoscopic exploration, and one lesion was found in the spleen. Then, a laparoscopic splenectomy (LS) confirmed a splenic metastasis from PFTC. The histopathological diagnosis showed that the splenic lesion was a high-differentiated serous carcinoma from PFTC metastasis. The patient recovered for over 1 year, with no tumor recurrence. This is the first reported case of an isolated splenic metastasis from PFTC. This case underlines the importance of serum tumor marker assessment, medical imaging examination, and history of malignancy during follow-up, and LS seems to be the optimal approach for isolated splenic metastasis from PFTC.